Entre a docência e o fazer artístico em artes visuais: a atuação de professores-artistas na educação básica de Belém e Ananindeua (Pará) - RODRIGUES, Ailzon Gonçalves (Universidade Federal do Pará, 2021)
From the understanding of the teacher-artist as a hybrid professional who has his actions moving between being a teacher and being an artist. And how the dialogical relationship of these professions brings benefits that, many times, can be suppressed in view of the obligations related to the teaching of Art. Searched in the performance of this professional reasons to avoid his detachment in Art and conciliate the artistic making with the pedagogical practices in basic education schools in the municipalities of Belem and Ananindeua. Therefore, the research aimed to understand the ways in which the relationship between the pedagogical practices of the teacher-artist in basic education and artistic productions develops. In addition to analyzing the contributions provided by the interaction of these activities and the methods used to realization of this conciliation. For this, the qualitative research, used as tools of data collection the semi-structured interview with six teachers from basic education of Art and the participant observation in the classroom. So, it was determined that the professionals to be investigated should have some characteristics, such as degree in Visual Arts or Artistic Education, working in basic education, regardless of the levels of experience with Art teaching and develop works and / or artistic experiments, regardless of the techniques or purpose with the art system. The teachers, under indication, would be previously investigated through the Lattes Curriculum before contacting them, which would allow to know more about the formation of these professionals, their historic of teaching and artistic performance. This way, the results showed how important the aesthetic and artistic experiences are for these professionals, which seek to keep them active, either in parallel activities or in the construction of pedagogical actions so that they can integrate the teaching-learning processes in Art together. Although this relationship has not been so evident in the actions in the classroom and does not have the support of the school, in the observations made it was not continuously present. So, it was understood that artistic making and teaching are activities inherent to the teacher-artist. For this reason, even in the face of the difficulties of several orders present in the basic education, this professional will seek ways for the coexistence of these processes in harmony, and feedback continuously